Is Silver Diamine Fluoride Effective in Preventing and Arresting Caries in Elderly Adults? A Systematic Review - Subbiah, Gireesh Kumar (J Int Soc Prev Community Dent, 2018)
AIM: Silver diamine fluoride (SDF) has invoked interest in recent times due to its remineralization capacity and non-invasive application procedure. The aim of this systematic review was to report the findings concerning the effectiveness of SDF in managing caries in the elderly adults. MATERIALS AND METHODS: A systematic search of publications was conducted using four databases: PubMed, MEDLINE, Embase, and CENTRAL. The key MeSH term combinations used were (silver diamine fluoride) AND (caries) AND (elderly). RESULTS: The review found only three well-conducted randomized controlled trials evaluating the effectiveness of SDF on root caries in community-dwelling elders. None of the studies addressed coronal caries. The effectiveness improved when combined with structured oral health education. CONCLUSION: The available limited evidence on SDF shows that it is effective in arresting and preventing root caries in the elderly. More high-quality studies need to be done to verify the effectiveness on coronal caries and long-term effects of SDF in the elderly with varying levels of dependency.